Effect of limited suckling on reproductive performance and milk production of cows and weight gains and suckling behavior of calves - Odde, Kenneth G.; Kiracofe, G.H.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
We used 109 Polled Hereford and percentage Simmental cows to evaluate limited suckling as an aid to induce cows to cycle after calving. Cows were allotted to: 1. once daily suckle; 2. twice daily suckle; 3. 48 hr calf removal (just before breeding season); and 4. controls (suckle ad libitum). Half of each group was implanted with Norgestomet 9 days before the breeding season. Limited suckling increased the number of cows showing estrus and conceiving early in the breeding season, and Norgestomet increased the percentage pregnant the first 21 days of the breeding season.
Keywords: Beef; Reproductive performance; Milk production; Weight gain